Effect of Polycythemia on Serum Lipid Profile and Oxidative Stress (Medico Legal Update, 2021)
Polycythemia is generally known as a disorder that affects the stem cells in the bone marrow and is characterizedby a high and excessive production of red blood cells. The current study was designed to investigate andinvestigate the relationship between the serum lipid profile and oxidative stress in polycythemia patients.,The study included examining 85 blood samples from both gender, males and females, for patients comingto Shatra General Hospital. During the study period, all of (Hb, PCV, MDA, TC, TG, HDL, LDL, andVLDL) were examined for both patients and control groups.The current study showed an increase in the incidence of polycythemia in males, while it decreased infemales, and the study showed that the incidence of polycythemia increased with age until it reached itspeak in the third age group 41-50 years, then the percentage gradually decreased to a minimum in the fifthage group 61-70 years .The results of the study recorded a significant increase P